2011
DOI: 10.2224/sbp.2011.39.8.1045
|View full text |Cite
|
Sign up to set email alerts
|

Does Women's Attitudinal State Body Image Improve After One Session of Posture Correction Exercises?

Abstract: Physically active people are usually more satisfied with their bodies than are sedentary people (Davis, 2002), but the influences exerted by physical activity on body image (BI) are not clear. In the current study, the effects of a posture correction exercise (PCE) session on attitudinal state BI were examined. We wanted to know if a single PCE session could have an immediate and positive influence on attitudinal state BI in women. Participants (217 women) were randomized into 2 groups either taking part in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As hypothesized, exercise led to a significant improvement ( d = 0.50) in evaluative/affective body image state. Additionally, changes on a perceptive body image state measure (adjusting distorted photos of oneself) were positively correlated with trait drive for thinness, shape and weight concerns, and global body dissatisfaction ( r = .36–.52; see also Scarpa, Nart, Gobbi, & Carraro, 2011). Perhaps even more relevant with regard to the present topic, Thomas, Tod, and Lavallee (2011) used a controlled crossover design to psychometrically assess MD symptomatology in weight-lifters twice: once after a resistance training session and once on a rest day.…”
mentioning
confidence: 95%
“…As hypothesized, exercise led to a significant improvement ( d = 0.50) in evaluative/affective body image state. Additionally, changes on a perceptive body image state measure (adjusting distorted photos of oneself) were positively correlated with trait drive for thinness, shape and weight concerns, and global body dissatisfaction ( r = .36–.52; see also Scarpa, Nart, Gobbi, & Carraro, 2011). Perhaps even more relevant with regard to the present topic, Thomas, Tod, and Lavallee (2011) used a controlled crossover design to psychometrically assess MD symptomatology in weight-lifters twice: once after a resistance training session and once on a rest day.…”
mentioning
confidence: 95%
“…Mosur-Kałuza S, Guszkowska M. Physical activity and body image of women: literature review Balt J Health Phys Act 2015; 7(3): [29][30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…While examining the influence of body-shaping on the body image among women, it has been observed that the body image improved as early as after one 60-minute training session [29].…”
Section: Positive Influence Of Physical Activity On the Body Imagementioning
confidence: 99%
See 1 more Smart Citation